Vivências e desafios do agir docente: questões para formação continuada à luz do interacionismo sociodiscursivo - Ramos, Ana Tália da Silva (2019)
The area of language teacher education in Brazil has received productive contributions intermediated by Applied Linguistics and its dialogue with different areas of knowledge (ALMEIDA FILHO, 1997; LEFFA, 1999; CELANI, 2003). The present study discusses the language of the teacher's work, more specifically, about the conflicts and challenges present in the teaching activity in the context of regular public education in Paraíba. Our central objective is to investigate how representations of two teachers about their experiences in continuing educations and how this process offers subsidies to face challenges in their teaching. Regarding the data generation of this research, two instruments were chosen: the questionnaire, to obtain the profile of our collaborators and the semi-structured interview that shows the central points of our work. To understand our object of study, we assume in this work the theoretical and methodological assumptions of Sociodiscursive Interactionism (BRONCKART, 1999, 2006, 2008; MACHADO, 2004) and the studies of Labor Sciences (AMIGUES, 2004; CLOT, 2007, 2010) In this way, we analyzes the interview texts that compose our corpus, from the perspective of the analysis categories of the ISD methodological framework, the thematic contents and the modalizations. Based on the results of our analysis, we observe that there is a gap between the projects of continuous training and the challenges faced by our collaborators. In this sense, we aim to contribute to delineate in the design of a continuing education, of a transdisciplinary nature, that considers the specific context. public school teacher, by promoting mainly, the strengthening of the collective work to deal with conflicts immanent in teaching activity.